2016
DOI: 10.1002/cjce.22522
|View full text |Cite
|
Sign up to set email alerts
|

Simplified flare combustion model for flare plume rise calculations

Abstract: The dispersion of plumes released from stacks depends on wind speed, plume emission rate, stack height, and other meteorological and stack variables. Plume rise is an important aspect of plume dispersion because it increases the apparent release height, which leads to lower ground-level concentrations. Plume rise linked with flare combustion has received only minimal attention in the literature to date, despite its importance. This study develops a numerical model of plume rise with flare combustion based on m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Very recent attempts to model such flames (Aboje et al, 2017;Damodara et al 2017) showed the influence of the composition of the natural gas and the validity of the chemical kinetic mechanism are of primary importance to predict the emitted species. Moreover, the flame characteristics such as temperature, height, and length, have a strong impact on the dispersion of the plume together with wind speed and other meteorological variables (Rahnama et al, 2016). All these parameters need to be taken into account when considering air field campaigns.…”
Section: Combustion Processes Involved In Oil Flarementioning
confidence: 99%
“…Very recent attempts to model such flames (Aboje et al, 2017;Damodara et al 2017) showed the influence of the composition of the natural gas and the validity of the chemical kinetic mechanism are of primary importance to predict the emitted species. Moreover, the flame characteristics such as temperature, height, and length, have a strong impact on the dispersion of the plume together with wind speed and other meteorological variables (Rahnama et al, 2016). All these parameters need to be taken into account when considering air field campaigns.…”
Section: Combustion Processes Involved In Oil Flarementioning
confidence: 99%
“…4 Wang et al 5 analyzed receptor configuration and measurement noise through numerical example analysis based on process hazard analysis software (PHAST). Rahnama et al 6 established a numerical model of the rise of flare combustion plumes based on matter, heat, mass, and momentum balance, which can be used to simulate the rise of plume flow in large area buoyancy sources. Wang et al 7 conducted a risk analysis on PHAST, according to the corresponding thermal radiation hazard standard.…”
Section: Introductionmentioning
confidence: 99%